210 Ventro-Lateral Motor Thalamus Abnormal Connectivity in Essential Tremor Before and After Stereotactic Radiosurgical Thalamotomy: A Resting-State fMRI Study. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Tuleasca, Constantin; Regis, Jean; Najdenovska, Elena; Witjas, Tatiana; Girard, Nadine; Champoudry, Jerome; Faouzi, Mohamed; Thiran, Jean-Philippe; Cuadra, Meritxell Bach; Levivier, Marc; Van de Ville, Dimitri
Abstract: INTRODUCTION: To evaluate functional connectivity (FC) of the ventro-lateral thalamus, a common target for drug-resistant essential tremor (ET), resting-state data were analyzed before and 1 yr after stereotactic radiosurgical thalamotomy (SRS-T), and compared against healthy controls (HC). METHODS: Seventeen consecutive patients and 10 HC were enrolled. Tremor network was investigated using ventro-lateral ventral (VLV) nucleus as region of interest (ROI), extracted using automated segmentation from pretherapeutic diffusion MRI. Temporal correlations of VLV at whole brain level were evaluated by comparing drug-naïve ET with HC, and longitudinally, 1 yr after SRS-T. Thalamotomy volume was always located inside VLV, and did not correlate with any of FC measures ( P  > .05). This suggested presence of longitudinal changes in VLV FC independently of thalamotomy volume. RESULTS: Pretherapeutic ET displayed altered VLV FC with left primary sensory-motor cortex, pedunculopontine nucleus, dorsal anterior cingulate, left visual association, and left superior parietal areas. Pretherapeutic negative FC with primary somatosensory cortex and pedunculopontine nucleus correlated with poorer baseline tremor scores (Spearmann = 0.04 and 0.01). Longitudinal study displayed changes within right dorsal attention (frontal eye fields and posterior parietal) and salience (anterior insula) networks, as well as areas involved in hand movement planning or language production. CONCLUSION: Our results demonstrated that ET and HC differ in their VLV FC to primary somatosensory and supplementary motor, visual association, or brainstem areas (pedunculopontine nucleus). Longitudinal changes display reorganization of dorsal attention and salience networks after thalamotomy. Beside attentional gateway, they are also known for their major role in facilitating a rapid access to the motor system.